Corporate Social Responsibilities Dimension Impact Towards Tax Avoidance - Tesalonika Avemaria Ineari Manich; Weli Weli (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
The purpose of this research is to analyze the impact of corporate social responsibility, as viewed from economic, environmental, and social dimensions, on tax avoidance practices. The research population comprises non-cyclical consumer sector manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. Data for this study were obtained from these companies' annual and sustainability reports. The research sample was selected using purposive sampling, resulting in 38 companies. Data analysis will involve Descriptive Statistical Analysis and Multiple Linear Regression Analysis using IBM Statistical Package for the Social Sciences (SPSS) version 25.0. The results of the data analysis indicate that only the variables related to the economic and environmental dimensions of corporate social responsibility impact tax avoidance practices. In contrast, social size does not influence tax avoidance practices.